Proton transfer pathways, energy landscape, and kinetics in creatine-water systems - Ivchenko, Olga; Whittleston, Chris S.; Carr, Joanne M.; Imhof, Petra; Goerke, Steffen; Bachert, Peter; Wales, David J. (Journal of Physical Chemistry B, 2014)
We study the exchange processes of the metabolite creatine, which is present in both tumorous and normal tissues and has NH2 and NH groups that can transfer protons to water. Creatine produces chemical exchange saturation transfer (CEST) contrast in magnetic resonance imaging (MRI). The proton transfer pathway from zwitterionic creatine to water is examined using a kinetic transition network constructed from the discrete path sampling approach and an approximate quantum-chemical energy function, employing the self-consistent-charge density-functional tight-binding (SCC-DFTB) method. The resulting potential energy surface is visualized by constructing disconnectivity graphs. The energy landscape consists of two distinct regions corresponding to the zwitterionic creatine structures and deprotonated creatine. The activation energy that characterizes the proton transfer from the creatine NH2 group to water was determined from an Arrhenius fit of rate constants as a function of temperature, obtained from harmonic transition state theory. The result is in reasonable agreement with values obtained in water exchange spectroscopy (WEX) experiments. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2020-02-18